Enhancement in isothermal crystallization and thermomechanical properties of poly(L‐lactic acid) filled with carbon fiber powder. Issue 9 (20th June 2020) - Chen, Li; Pang, Xiujiang; Yu, Guangshui; Liu, Jiwen; Hu, Haiqing; Zhao, Jian
Abstract: Carbon fiber (CF) is one good carbon filler for polymer modification. The aspect ratio of CF is supposed to affect the modification. In this research, the dependence of the crystallization behavior and thermomechanical properties of poly(L‐lactic acid) (PLLA) upon the aspect ratio of CF was investigated systematically by utilizing various characterizations, including polarized light microscopy, scanning electron microscopy, wide‐angle X‐ray diffraction, differential scanning calorimetry, X‐ray photoelectron spectroscopy, static and dynamic mechanical properties, thermal stability, and thermal conductivity. Results indicated that carbon fiber powder (CFP) with smaller aspect ratio displayed more obvious heterogeneous nucleation and accelerating effect on the isothermally melt crystallization of PLLA matrix than normal CF with bigger aspect ratio. In the meanwhile, CFP had less adverse effect on the perfection of α crystal of PLLA than CF. Compared with PLLA or PLLA/CF composite, the tensile strength or the elongation at break of PLLA/CFP composite could be enhanced through proper annealing treatment. The bigger upshift of T g determined by dynamic mechanical analysis indicated superior adhesion between PLLA and CFP in PLLA/CFP composites to that in PLLA/CF composites. Besides, CFP improved the thermal stability and thermal conductivity of PLLA composites more efficiently than CF. Abstract :